The continuation of a civic obligation? The Athenian trierarchy in the late third century BCE - Ammitzbøll Thomsen, Christian (Classica et Mediaevalia, 2024)
While it is clear that third-century BCE Athens continued to maintain a fleet, albeit a much smaller one than in previous centuries, it is usually believed that the Athenian trierarchy had been abolished during the reign of Demetrios of Phaleron (318-308 BCE). However, an honorific decree (I.Rhamnous 31) from Rhamnous, voted for a trierarch by an association of sailors, gives evidence for the existence of a late-third-century BCE trierarchy, which preserved the basic features of its Classical predecessor. The Athenians continued to appoint trierarchs for year-long terms, expected them to serve in person and required them to pay for the maintenance of the ship in their care. The permanent assignment to the ship of a crew, which formed an association and acted as an agent of the Athenian state, represented an innovation.